Millions of Bangladeshi Children Missed Their Scheduled Vaccination Amidst COVID-19 Pandemic - Hanifi, Sayed Manzoor Ahmed; Jahan, Nujhat; Sultana, Nazia; Hasan, Sharif-Al; Paul, Ashish; Reidpath, Daniel D. (Frontiers in Public Health, 2022)
The Government of Bangladesh imposed a movement control order as a mass quarantine strategy to control the outbreak of coronavirus disease 2019 (COVID-19). Adherence to the home quarantine may put children at risk by missing routine vaccination. In this study, we investigated the impact of COVID-19 on child routine immunization in a rural area of Bangladesh and consider the broader implications. Data for this study comes from the Chakaria Health and Demographic Surveillance System (HDSS) of icddr,b with a population of 90,000 people residing in 16,000 households in 49 villages in a rural, coastal area of Southeast Bangladesh. We used an explanatory sequential mixed methods design which involved two phases: first, between March 1, 2020, and May 31, 2020, we observed 258 outreach sessions of 86 EPI centers. We calculated the number of Expanded Program on Immunization (EPI) outreach sessions suspended and the number of children who missed their routine vaccination due to the COVID-19. We extrapolated the number of Bangladeshi children who missed their routine vaccination using Chakaria HDSS observations. In the second phase, we conducted in-depth interviews to explain the quantitative results. The EPI outreach session declined to 74.42% (95% CI 63.97-83.22), 10.45% (95% CI 5.00-18.94), and 3.45% (95% CI 1.00-9.75) from 2019 levels in March, April, and May 2020, respectively. By extrapolation, in Bangladesh, between March and May 2020, 3.2 million children missed their scheduled vaccination compared to 2019. Results from in depth interviews showed that the unwillingness of villagers to hold EPI outreach sessions and the absenteeism of the vaccinators due to social distancing recommendations and lack of personal safety measures were the main reasons for the discontinuation of the EOS. Resuming EPI outreach sessions and introducing a special catch-up program is essential to prevent future outbreaks and deaths due to vaccine-preventable diseases in Bangladesh and the countries where children missed their routine vaccination due to COVID-19. This health system failure should be considered a factor in all future pandemic preparedness plans.